Awareness about Dyslexia among Public School Teachers of Muzaffaraba - Maliha Nasir (JIE, 2024)
Teachers generally must deal with students who have various types of problems in learning. These problems may be symptoms of some specific learning disabilities like dyslexia that is a languagebased disorder which involves difficulty in reading fluently, word recognition, decoding, spelling and sometime difficulty in speech.